1996
DOI: 10.1038/bjc.1996.193
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of Stealth liposomal doxorubicin in AIDS-related Kaposi's sarcoma

Abstract: Summary The utility of current chemotherapeutic regimens in the treatment of AIDS-related Kaposi 44 (18.5%) had stable disease and two (0.8%) had disease progression. SL-DOX was well tolerated: ten patients discontinued therapy because of adverse events, in four cases because of neutropenia. Grade 3 or 4 neutropenia occurred after 281 of 2023 cycles (13.9%) but involved 137 of 240 patients (57.1%) for whom data were available. SL-DOX has substantial activity in AIDS-KS. Best response is typically seen after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
3

Year Published

1998
1998
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(49 citation statements)
references
References 27 publications
1
44
3
Order By: Relevance
“…Liposomes are membrane-enclosed vesicles composed of a lipid bilayer shell (which can trap hydrophobic and amphipathic drugs) surrounding an aqueous core (which can encapsulate hydrophilic drugs) [19][20][21]. In contrast to microbubbles, liposomes have been shown to efficiently carry drugs such as doxorubicin and vincristine [22][23][24], and intravenous injection of drug-carrying liposomes can increase accumulation at the tumor site by 50 to 100 fold compared to the administration of free drug [25][26][27]. Moreover, monodisperse liposomes can be manufactured with an optimized diameter, typically chosen to be near 100 nm to maximize extravasation from tumor vasculature and fusion with cell membranes.…”
Section: Introductionmentioning
confidence: 99%
“…Liposomes are membrane-enclosed vesicles composed of a lipid bilayer shell (which can trap hydrophobic and amphipathic drugs) surrounding an aqueous core (which can encapsulate hydrophilic drugs) [19][20][21]. In contrast to microbubbles, liposomes have been shown to efficiently carry drugs such as doxorubicin and vincristine [22][23][24], and intravenous injection of drug-carrying liposomes can increase accumulation at the tumor site by 50 to 100 fold compared to the administration of free drug [25][26][27]. Moreover, monodisperse liposomes can be manufactured with an optimized diameter, typically chosen to be near 100 nm to maximize extravasation from tumor vasculature and fusion with cell membranes.…”
Section: Introductionmentioning
confidence: 99%
“…These results can probably be explained by the difference in doses because the adverse effects with this molecule are known to be dose dependent. 28 Wollina et al 17 used 20 mg/m 2 as the dose for 28 patients in their study, 20 to 30 mg/m 2 for 4 patients, and 40 mg/m 2 for 2 patients, whereas all of our patients received a dose of 40 mg/m 2 . In our study we observed 4 serious infections (3 cases of S aureus septicemia and 1 pneumopathy).…”
Section: Commentmentioning
confidence: 99%
“…Impressive response rates to pegylated liposomal chemotherapeutic agents have been obtained in mice bearing mouse mammary tumours and human tumour xenografts (reviewed in Working et al, 1994). In clinical trials, pegylated liposomes containing doxorubicin have been shown to be active against AIDS-related Kaposi's sarcoma, with response rates in excess of either free doxorubicin or conventional combination chemotherapy (Bogner et al, 1994;Harrison et al, 1995;Goebel et al, 1996). Trials of liposomal chemotherapy in patients with a variety of solid tumours are currently under way.…”
mentioning
confidence: 99%